Product market relationships and cost of bank loans: evidence from strategic alliances - Yiwei Fang; Bill Francis; Iftekhar Hasan; Haizhi Wang (Bank of Finland, 2011)
This paper examines the effects of strategic alliances on non-financial firms bank loan financing. We construct several measures to capture firms alliance activities using the frequency of alliance activities, the prominence of the alliance partner and the relative networking position in the overall alliance network. We find that firms with active alliance involvement experience a lower cost of debt from banks. We also document that allying with a prestigious partner (ie S&P 500 firms) can provide an endorsement effect and benefit the borrowers by reducing the price of bank loans. Moreover, a borrowing firm positioned at the centre of an alliance network enjoys a lower cost of bank loans. Finally, we find that borrowing firms with alliance experience are less likely to use collateral and covenants in their loan contracts.
URN:NBN:fi:bof-20140807543
Keywords: 330